Impact of UPFC-based damping controller on dynamic stability of Iraqi power network - Hassan, L.H.; Moghavvemi, M.; Mohamed, H.A.F. (Academic Journals, 2011)
The work of this paper is a hopeful attempt to rectify poor damping issue of the Iraqi National Super Grid System (INSGS). Without proper damping control these oscillations drive the system toward instability following severe disturbances. In this paper, a Unified Power Flow Controller (UPFC)-based damping controller was proposed to improve the dynamic stability of the INSGS. The system with UPFC installed in different sectors was represented by the linearized Phillips-Heffron generator model. The excitation phase angle was used as input control signal to the UPFC. PI controller was applied to the design of the damping controller. The power system with the UPFC was tested in different sectors under different loading conditions and disturbances using the MATLAB Simulink program. Simulation results demonstrated that the UPFC can work successfully with INSGS in damping low-frequency oscillations and improving the dynamic stability and voltage profiles. In addition, the proposed approach provided higher performance when compared to a conventional PSS.